Diversity and Distribution of Macrofungi in some Sacred Groves of Bankura District, West Bengal, India - Nayak, Atanu; Bhakat, Ram Kumar; Pandit, Prasanta Kumar (Indian Forester, 2025)
Sacred groves are traditionally conserved sites which act as safe houses for local biodiversity. Macrofungi are a diverse and ecologically important group of fungi that play various roles in ecosystems though they have received less attention in practice. This work is the first attempt to provide baseline information about assemblage, diversity and distribution pattern of macrofungi in ten isolated sacred groves situated in ten different Civil blocks of Bankura district, West Bengal. These groves conserve 66 species (5 belonging to Ascomycota and 61 belonging to Basidiomycota) of macrofungi, of which a significant portion (69.69%) is saprophytic in nature. Out of those 66 species, only 5 species belong to Ascomycota and the remaining 61 belongs to Basidiomycota. Among the surveyed groves, Simladihi Jaher Than in-houses the maximum number (37) of macrofungi whereas Raidihi Gram than conserve lowest number (7) of the same. Majority of the species (36 spp.) fall into the frequency class A and 21 species belong to frequency class B. However, 3 species show highest frequency percentage (70%). 23 species are consumed as protein rich food by the locals. Out of the edible fungi, some are sold in the nearby market for the livelihood. Some additional observations regarding the threats and status of these groves are also noted. In future, multidimensional data should be collected and processed, to effectively make functional clusters of sacred groves and accordingly to plan a better management strategy.